Pemberian makanan pendamping ASI (MP-ASI) dengan status gizi pada bayi usia 6-12 bulan - Linawati Novikasari; Hardono Hardono; Heru Sapto Adi (Holistik Jurnal Kesehatan, 2020)
Complementary foods on infant breast milk intake and nutrition status in infants 6 to 12 months oldBackground: Based on pre-survey data for January 2019 in the Karang City Health Center for 30 infants aged 6-12 months, 12 infants (40%) had normal nutritional status, and 18 infants (60%) with undernourished status, based on data from interviews with people parents who have children aged 6-12 months with poor nutritional status, 10 mothers (55.5%) said they did not know about the importance of giving MP-ASI such as the right time in giving MP-ASI, food menu for MP-ASI, and the portion MP-ASI for babies, and 8 mothers (44.5%) said they only gave formula milk as a substitute for breast milk.Purpose: Knowing to the relationship of complementary feeding (MP-ASI) with nutritional status in infants aged 6-12 months in the working area of Karang Bandar Lampung Health Center in 2019.Method: Quantitative research type. Analytic survey research design with cross sectional design. The population of all mothers who have infants aged 6-12 months in the working area of Karang Bandar Lampung Health Center in 2019 amounted to 86 respondents, a sample of 86 respondents. The sampling technique used is total sampling. Chi-square test data analysis.Results: Known in the working area of Karang Bandar Lampung Health Center in 2019, there were 45 respondents given MP-ASI well, 27 respondents (60.0%) had good nutrition and 18 respondents (40.0%) had poor nutrition, while there were 41 respondents given MP-ASI are not good, 10 respondents (24.4%) have good nutrition and 31 respondents (75.6%) have poor nutrition. Statistical test results, obtained p-value 0.002 or p-value <0.05.Conclusion: There is a relationship between complementary feeding (MP-ASI) with nutritional status in infants aged 6-12 months in the working area of Karang Bandar Lampung Health Center in 2019 with a p-value of 0.002. It is expected that the Puskesmas will be able to make a list of MP-ASI gift menus and provide infrastructure facilities on the MP-ASI menu according to the baby's needs.Keywords: Complementary foods; Breast milk; Nutritional status; Infants 6 to 12 months oldPendahuluan: Berdasarkan data prasurvey bulan Januari 2019 Di Puskesmas Kota Karang terhadap 30 bayi yang berusia 6-12 bulan, diketahui 12 bayi (40%) status gizi normal, dan 18 bayi (60%) dengan status gizi kurang, berdasarkan data wawancara terhadap orang tua yang mempunyai anak usia 6-12 bulan dengan status gizi kurang, 10 ibu (55,5%) mengatakan kurang mengetahui tentang pentingnya pemberian MP-ASI seperti waktu yang tepat dalam pemberian MP-ASI, menu makanan untuk MP-ASI, serta porsi MP-ASI untuk bayi, dan 8 ibu (44,5%) mengatakan hanya memberikan susu formula sebagai pengganti ASI.Tujuan: Diketahui hubungan pemberian makanan pendamping ASI (MP-ASI) dengan status gizi Pada Bayi usia 6-12 bulan Di Wilayah Kerja Puskesmas Kota Karang Bandar Lampung Tahun 2019.Metode: Jenis penelitian kuantitatif. Rancangan penelitian survey analitik dengan desain cross sectional. Populasi seluruh ibu yang mempunyai Bayi usia 6-12 bulan yang berada di Wilayah Kerja Puskesmas Kota Karang Bandar Lampung Tahun 2019 berjumlah 86 responden, Sampel 86 responden. Teknik sampling yang digunakan total sampling. Analisa data uji chi-square.Hasil: Diketahui bahwa di wilayah kerja Puskesmas Kota Karang Bandar Lampung Tahun 2019, terdapat 45 responden yang diberikan MP-ASI dengan baik, 27 responden (60,0%) mengalami gizi baik dan 18 responden (40,0%) mengalami gizi kurang baik, sedangkan terdapat 41 responden yang diberikan MP-ASI kurang baik, 10 responden (24,4%) mengalami gizi baik dan 31 responden (75,6%) mengalami gizi kurang baik. Berdasarkan hasil uji statistik, didapatkan p-value 0,002 atau p-value < 0,05.Simpulan: Ada hubungan pemberian makanan pendamping ASI (MP-ASI) dengan status gizi pada bayi usia 6-12 bulan Di Wilayah Kerja Puskesmas Kota Karang Bandar Lampung Tahun 2019 dengan p-value 0,002. Diharapkan kepada pihak Puskesmas agar dapat membuat daftar menu pemberian MP-ASI dan menyediakan fasilitas sarana prasarana tentang menu MP-ASI sesuai dengan kebutuhan bayi.